Enhancing Vocational Students' Work Competitiveness through Work-Based Project Learning: A Quasi-Experimental Study in West Java, Indonesia - Pratama, Yudhistira Anugerah; Audina Margaretha Putri; Isabelle van den Berg (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study aims to examine the effectiveness of the work-based project learning model in enhancing vocational students’ work competitiveness in the dimensions of technical skills, problem-solving ability, collaboration and communication, and self-directed learning. This study also examines how students’ involvement in work-based projects can strengthen their readiness to face industrial demands. Design/methods – This study used a quasi-experimental design with a mixed-methods approach through a pretest-posttest control group design. The research involved 180 vocational high school students in West Java, Indonesia, who were divided into an experimental group and a control group. The experimental group participated in work-based project learning for 16 weeks, while the control group received conventional instruction. Quantitative data were analyzed using ANCOVA to examine differences in learning outcomes between groups, while qualitative data were analyzed through thematic analysis of interviews, reflection journals, classroom observations, and project documents. Findings – The results show that students in the experimental group achieved significantly higher competency outcomes than those in the control group. The effect sizes were large for technical skills (d = 1.31), problem-solving (d = 1.25), collaboration and communication (d = 1.21), and self-directed learning (d = 1.28). A total of 85–87% of students in the experimental group reached the good or excellent category, while only 52–65% of students in the control group achieved the same level. In addition, this learning model encouraged students’ active engagement, increased self-confidence, and supported the formation of a clearer professional identity. These findings confirm that work-based project learning is effective in improving vocational students’ work competitiveness through authentic learning experiences, industry collaboration, and integrated competency development.